Characterization and optimization of levan production by Bacillus subtilis NATTO - Dos Santos, Leandro Freire; Bazani Cabral De Melo, Fernando Cesar; Martins Paiva, Wagner Jose; Borsato, Dionisio; Corradi Custodio Da Silva, Maria De Lourdes [UNESP]; Pedrine Colabone Celligoi, Maria Antonia (Ars Docendi, 2013)
Exopolysaccharides are in evidence due to their applications, especially in the food industry. The levan is an exopolysaccharide composed by fructose residues, which has been used as stabilizer, carrier of flavours and thickener for foods. Optimized conditions for the levan production are necessary to increase its industrial application. This study aimed to optimize the production of levan synthesized by B. subtilis isolated from Japanese food called Natto by factorial design and response surface methodology, as well as the molecular weight, rheological behaviour and toxicity characterization. In view of the independent variables studied, the experiment showed the best results at: sucrose (400 g/L) and culture time (16 h); 111.6 g/L of levan. In these optimized condition the sample presented two molecular weights of levan, 568.000 Da and <50.000 Da, corresponding to 13.39% and 86.61% respectively. The viscosity assay by varying the shear rate demonstrated that the levan presents a Newtonian behaviour and no toxic or genotoxic effects were observed by increasing the frequency of micronuclei in CHO-K1 cells and MTT.
Keywords: Levan; factorial design; molecular weight; rheological behaviour; cytotoxicity; Bacillus subtilis